Pengaruh Lingkungan Kerja Terhadap Kinerja Pegawai dengan Motivasi Kerja Sebagai Variabel Intervening di Kantor Dinas Perhubungan Kabupaten Musi Rawas - Fika Puspa; Suyadi Suyadi; Rudi Azhar (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to understand how the work environment affects employee performance, with work motivation acting as an intervening variable, at the Musi Rawas Regency Transportation Office. The research uses a quantitative approach, collecting data through questionnaires. The population consists of all 80 employees at the office, and a saturated sample technique is used. The data is analyzed using the Partial Least Square (PLS) method with the help of SmartPLS software. The results show that the work environment has a positive and significant effect on employee performance. Additionally, the work environment also positively and significantly affects employee performance through work motivation as an intervening variable. The study recommends that institutions should create a supportive work environment and improve employee motivation to encourage better performance.